AN ANALYSIS OF THE COMPATIBILITY OF LET'S TALK TEXTBOOK WITH THE SCHOOL LEVEL-BASED CURRICULUM - AN-NISA, MINA NUR (2011)
This research paper is mainly intended to find out whether the English textbook used for the second year student of junior high school English on Let's Talk develops the skills suggested by the School Level -based Curriculum and communicative exercises. In line with the objectives of the research, the writer uses a descriptive method. In collecting the data, she used document as data source. The data were analyzed by these steps: (1) finding out the kinds of skill and communicative exercise available on the textbook, (2) classifying them, (3) analyzing them, (4) counting and adding them, (5) giving percentage from the total number, (6) Judging whether the data are appropriate with indicators in School Level -based Curriculum or not, and (7) drawing conclusion and proposing suggestions. The result of the analysis shows that the percentage of the appropriateness of the skills developed in the textbook is 65, 11% (listening: 51, 69%; speaking: 63,38%; reading: 75%; writing: 90%). It means that the textbook is compatible with the School Level -based Curriculum in developing skills. This research shows that the textbook entitled Let's Talk is good materials to support the learning process especially in speaking, reading and writing. The materials of listening skill in this textbook are not adequate, so the listening teaching-learning process needs the other material to support the listening lesson. While the percentage gained in developing the communicative exercises is 60%. The result of study implies that the teacher should supply the textbook analyzed with other books which much better in order to achieve the goal of teaching English. The writer of the textbook should revise the textbook and add more text, activities and communicative exercises to increase the quality of the textbook.